Variations of groundwater storage in different basins of China over recent decades - Yin, Zijun; Xu, Yuyue; Zhu, Xiaoyun; Zhao, Jianwei; Yang, Yaping; Li, Jin (Journal of hydrology (Amsterdam), 2021)
•This study estimated groundwater storage information of China.•The groundwater storage was certificated to be reliable and accurate.•The causes of groundwater storage changes in different basins were analyzed. As an important freshwater resource, groundwater is of great significance to agriculture, industry, and daily life. The investigation of groundwater storage (GWS) in different regions of China is critical for water resource management and conservation. However, previous studies used different methods and data to monitor GWS in different regions of China, which made their results difficult to compare and cross validate. Here, we used a unified method by the Gravity Recovery and Climate Experiment (GRACE) satellite data and global models to study the variations of GWS in 10 major basins in China from April 2002 to December 2016. Results showed that GWS in the i) Songhua River basin (SRB), Liao River basin (LRB), Haihe River basin (HRB), Yellow River basin (YRB), Huaihe River basin (HHRB), and southeast basin (SEB) exhibited decreasing trends, ii) Yangtze River basin (YZRB) and Pearl River basin (PRB) presented increasing trends, and iii) southwest basin (SWB) and continental basin (CB) displayed both decreasing and increasing trends during the study period. These results were validated by comparing them with a large number of previous studies, which revealed that they were accurate and reliable. Comparing with the climate data and bulletin data, the analysis of causes for these trends indicated that drought and irrigation water-use led to a decline in GWS in several basins of northern China. The decreasing trend of GWS in the SEB was related to water use for production, whereas groundwater recharge from precipitation drove the increasing trends of GWS in the YZRB and PRB. In contrast, the wide geographical areas and complex factors of the SWB and CB led to the increasing–decreasing trends of GWS. This study enriches the GWS for China over the past decade, especially for SEB, PRB, and CB with rare GWS information. It will be helpful for the country’s groundwater resource management and systematic water conservation.